Caracterización morfológica y evaluación agronómica de 8 líneas de amaranto (amaranthus sp.) provenientes de Rusia en el barrio Tigualo (Salcedo) y en el barrio Las Manzanas (sigchos). Cotopaxi. 2014 - Grandes Román, Gladys Nathaly (2015)
The research aimed to characterize morphologically and evaluate agronomically 8 lines of amaranth (Amaranthus sp.) from Russia in Tigualo town (Salcedo) and Las Manzanas neighborhood (Sigchos) in Cotopaxi province . For the implementation of the test a design in accordance with DBCA factorial was used 2 x 8 with 3 replications, for agronomic morphological data, it was used descriptors of Amaranth of IPGRI according to the phenological State of the plant. It was used the analysis of variance for the quantitative variables. And 5% Tunkey was used to determine the ranges. This Select the best lines of amaranth, based on the degree of adaptability, earliness, size of grain, high performance, in two different agro-ecological environments. Agronomic data recorded showed highly significant differences between locations and lines which show that they developed depending on their varietal characteristics of each, which could also be seen in the morphological characters that there were differences in color….